Chlamydia trachomatis utilizes the mammalian CLA1 lipid transporter to acquire host phosphatidylcholine essential for growth. (16th October 2015) - Cox, John V.; Abdelrahman, Yasser M.; Peters, Jan; Naher, Nirun; Belland, Robert J.
Summary: Phosphatidylcholine is a constituent of Chlamydia trachomatis membranes that must be acquired from its mammalian host to support bacterial proliferation. The CLA1 (SR‐B1) receptor is a bi‐directional phosphatidylcholine/cholesterol transporter that is recruited to the inclusion of Chlamydia ‐infected cells along with ABCA1. C. trachomatis growth was inhibited in a dose‐dependent manner by BLT‐1, a selective inhibitor of CLA1 function. Expression of a BLT‐1‐insensitive CLA1(C384S) mutant ameliorated the effect of the drug on chlamydial growth. CLA1 knockdown using shRNAs corroborated an important role for CLA1 in the growth of C. trachomatis . Trafficking of a fluorescent phosphatidylcholine analogue to Chlamydia was blocked by the inhibition of CLA1 or ABCA1 function, indicating a critical role for these transporters in phosphatidylcholine acquisition by this organism. Our analyses using a dual‐labelled fluorescent phosphatidylcholine analogue and mass spectrometry showed that the phosphatidylcholine associated with isolated Chlamydia was unmodified host phosphatidylcholine. These results indicate that C. trachomatis co‐opts host phospholipid transporters normally used to assemble lipoproteins to acquire host phosphatidylcholine essential for growth. Abstract : The obligate intracellular pathogen Chlamydia trachomatis is the leading bacterial cause of sexually transmitted infections. The growth of Chlamydia within infected cells is dependent upon its ability to acquire phosphatidylcholine, a major lipid in chlamydial membranes, from the host. We show that Chlamydia trachomatis co‐opts the host phospholipid transporters, CLA1 and ABCA1, which are normally involved in the biogenesis of high density lipoproteins to acquire host phosphatidylcholine essential for growth. Chlamydial growth is dependent upon the lipid transport activity of CLA1. The growth of C. trachomatis (green) within infected HeLa cells (left panel) is inhibited in cells treated with BLT‐1, an inhibitor of the host CLA1 phospholipid transporter. BLT‐1 exerted a similar inhibitory effect on chlamydial growth in HeLa cells transfected with a wild type CLA1‐DsRed fusion (middle panel). Chlamydial growth was restored in BLT‐1 treated cells that were transfected with a BLT‐1 resistant mutant of CLA1, CLA1(C384S)‐DsRed (right panel). Arrows point to inclusions in infected cells. Note large inclusion filled with multiple Chlamydia in cell transfected with the CLA1(C384S)‐DsRed mutant. Nuclei are stained with Hoechst (blue).